2018
DOI: 10.4103/ijnmr.ijnmr_17_17
|View full text |Cite
|
Sign up to set email alerts
|

The barriers and challenges of applying new strategies in the clinical evaluation of nursing students from the viewpoints of clinical teachers

Abstract: Background:Numerous studies have emphasized the use of new approaches in clinical evaluation. However, there are some challenges and barriers to applying these new approaches. The aim of the present study was to investigate the barriers and challenges of applying new strategies in the clinical evaluation of nursing students from the viewpoints of clinical teachers.Materials and Methods:This cross-sectional study was conducted among 151 clinical teachers. A researcher-made questionnaire was used to collect data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Ahmadpour et al also examined the correlation of ROP with CRIB score. Of the 256 studied neonates, 180 (70%) had retinopathy in some degrees, of which 56 (31.11%) required treatment, although the relationship between CRIB score and severity of retinopathy was insignificant (P = 0.152); hence, the CRIB cannot predict the severity, progression, or remission of retinopathy (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Ahmadpour et al also examined the correlation of ROP with CRIB score. Of the 256 studied neonates, 180 (70%) had retinopathy in some degrees, of which 56 (31.11%) required treatment, although the relationship between CRIB score and severity of retinopathy was insignificant (P = 0.152); hence, the CRIB cannot predict the severity, progression, or remission of retinopathy (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Torabizadeh and Moradi expressed similar problems in clinical evaluation. Scientific sources state that using the OSCE, MINI-CEX DOPS test is very useful (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study conducted by Steenaart (2019) also showed that the use of new educational methods can increase the knowledge and attitude of nurses in the area of organ donation, which was consistent with the results of this study (38)(39)(40)(41)(42). The results of the studies conducted by Srinivasula et al (2018) and Sugumar et al (2017) and Marqués-Lespier JM (2013) also showed that educational interventions play an important role in increasing the knowledge and attitude of staffs of different medical departments in brain death and organ donation processes and it is necessary to implement educational programs continuously to increase knowledge and improve the performance of the staffs (43)(44)(45)(46). The results of the study conducted by Aghayan et al (2009) to evaluate the effect of the lecture-based educational workshop on the nurses' knowledge and attitudes on donation in Tehran (47,48), showed that the implementation of the educational program had no effect on the attitude of nurses and no relationship was found between the knowledge and attitude, which was not consistent with the result of the present study (49).…”
Section: Discussionmentioning
confidence: 99%
“….001 17.43±2.39 19.27±2.63 10.38 ±2.39 intervention .034 12.78 ±2.63 12.47±2.54 10.48±2 43. Comparison of the attitude score of nurses in the area of organ donation in the test and control groups in the three stages of before, immediately and one month after the intervention…”
mentioning
confidence: 99%